GOOD GROWTH how brands win with social impact. - RODRIGUEZ-VILA, OMAR (ROUTLEDGE, 2025)
Business has a sustainability problem-and sustainability has a business problem, as many companies are fearful of engaging with social and environmental issues, owing to the costs and risks.Addressing these dual challenges head on, this book provides a blueprint for putting social and environmental benefits at the center of a company's growth agenda. Many sustainability books offer 30,000-foot strategic views and broad-brush guidance on the business of "doing well by doing good," but here is a ground-level guide for profitably integrating social and environmental benefits into individual products and brands. The book introduces the rapidly emerging phenomenon of social impact markets and shows how companies can capitalize on these new pockets of consumer demand through focused strategy, data-informed implementation, and a clear eye on the future, including how digital technologies are creating new ways for brands to expand their social impact and make social mission a central element of competitive strategy.Weaving together rich case studies and practical tools, this research-backed and real-world-ready guide fills a critical niche: a hands-on strategy playbook for the executives charged with driving brands' top-line growth, making it essential reading for C-suite leaders, R&D, product, and brand managers, board members, NGOs, as well as MBA and executive education students.